Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1017/s1355617708080053
|View full text |Cite
|
Sign up to set email alerts
|

Executive functioning in preschool children born very preterm: Relationship with early white matter pathology

Abstract: Despite evidence for executive dysfunction in school-aged preterm children, less is known about the early development of these difficulties or their underlying neuropathology. This study used prospective longitudinal data from a regional cohort of 88 very preterm and 98 full-term comparison children to examine the executive functioning (EF) of preschool children born very preterm. The relationship between the severity of neonatal cerebral white matter (WM) abnormalities on magnetic resonance imaging (MRI) at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 46 publications
7
94
2
2
Order By: Relevance
“…The combination of deficiencies in both mathematics and visual-perceptual skills, together with the high prevalence of abnormalities in white matter (Edgin et al, 2008), raises the possibility that MLD in these children are similar to the nonverbal LD described by Rourke (1993). However, injury to other brain structures, such as the hippocampus and parietal gray matter (Isaacs et al, 2000(Isaacs et al, , 2001 may also contribute to MLD.…”
Section: Discussionmentioning
confidence: 98%
“…The combination of deficiencies in both mathematics and visual-perceptual skills, together with the high prevalence of abnormalities in white matter (Edgin et al, 2008), raises the possibility that MLD in these children are similar to the nonverbal LD described by Rourke (1993). However, injury to other brain structures, such as the hippocampus and parietal gray matter (Isaacs et al, 2000(Isaacs et al, , 2001 may also contribute to MLD.…”
Section: Discussionmentioning
confidence: 98%
“…Results showed that preterm children had inhibition defi cits, as measured by responses to a Delayed Alternation Task. Edgin, Inder, Anderson, Hood, Clark, and Woodward ( 2008 ) examined inhibition and shifting abilities of 88 preterm children (GA of < 33 weeks), using scores on a Multi-Search Multi-Location task for 2-year-old children, and Detour Reaching Box scores for 4-year-old children. They concluded that preterm children present inhibition and shifting defi cits as early as preschool age, and that these defi cits are linked with white matter abnormalities.…”
Section: Attentional Network Effi Ciency In Preterm Childrenmentioning
confidence: 99%
“…VPT/VLBW children at the ages of 5 to 12 years perform poorer than full-term controls in inhibition tasks compared with same-aged controls [4,8,16]. Poor inhibition skills in VPT/VLBW children have been linked to cerebral lesions (e.g., haemorrhage) [21] and white matter abnormalities (e.g., reduction of white matter volume, ventricular dilatation, thinning of the corpus callosum, and delay in myelination) [15].…”
Section: Introductionmentioning
confidence: 99%
“…For that reason, shifting is suggested to be more complex than inhibition and WM [5]. Some studies have reported deficiencies in shifting of younger [8,15,39] and older VPT/VLBW children [4,40], as well as young VPT/VLBW adults [41]. In other studies, equal performance levels of shifting have been found in VPT/ VLBW and control children [37].…”
Section: Introductionmentioning
confidence: 99%